Pengaruh pertumbuhan ekonomi & upah minimum terhadap kemiskinan di kota surabaya - Qitfirul Aziz Januar; Imam Mashuri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of economic growth and minimum wages on poverty rates in the city of Surabaya. Although Surabaya is the center of economic growth in East Java, poverty is still a problem that requires serious attention. This study uses a quantitative approach with secondary data from the Central Statistics Agency (BPS) and related agencies during the period 2018–2024. The analysis method used is multiple linear regression to determine the relationship between the independent variables (economic growth and minimum wages) and the dependent variable (poverty rate). The results of the study indicate that economic growth has a significant and negative effect on poverty rates, meaning that increasing economic growth tends to reduce poverty rates. Meanwhile, the minimum wage does not show a significant effect, indicating that the minimum wage policy has not been fully effective in reducing poverty rates in Surabaya. These findings demonstrate the importance of synergy between inclusive economic growth and targeted social policies to reduce poverty sustainably.